Predictors and impacts of colostrum consumption by 4 h after birth in newborn beef calves. (October 2017) - Homerosky, E.R.; Timsit, E.; Pajor, E.A.; Kastelic, J.P.; Windeyer, M.C.
Highlights: Calves with a weak suckle reflex had 41.6 times greater odds of failing to consume colostrum by 4 h after birth. Suckle reflex and calving ease was used in combination to predict colostrum consumption by 4 h after birth. Consuming colostrum by 4 h after birth positively impacted transfer of passive immunity and preweaning health of beef calves. Abstract: Newborn beef calf vigor is a vital survival characteristic that promotes timely colostrum consumption. Modified APGAR scores intended to identify compromised calves are not widely adopted due to impracticality, inconsistent associations with blood gas disturbances, and unclear recommendations for intervention. The objectives were to: (1) determine differences in at-birth blood parameters between calves that were successful in colostrum consumption by 4 h (CC4) compared to those that failed; (2) develop a Beef Calf Vigor Assessment by determining calving characteristics and clinical examination parameters associated with CC4; and (3) evaluate impacts of failed CC4 on transfer of passive immunity and treatment risk. As a predictor for CC4, suckle reflex had the highest specificity (98%), whereas calving ease had the highest sensitivity (89%). Calves with a weak suckle reflex had 41.6 (95% CI: 7.4–787.5) times greater odds of failed CC4 compared to calves with a strong suckle reflex ( P < 0.0001). Calves with failed CC4 had lower serum IgG ( P = 0.01), had lower odds of acquiring optimal passive immunity (>24 g/L serum IgG; OR = 6.4, 95% CI: 1.2–34.4; P = 0.02), and higher odds of being treated (OR = 2.8, 95% CI: 1.1–7.4; P = 0.03) than those that succeeded. Measuring suckle reflex in combination with calving ease was a quick and easy method to assess newborn beef calf vigor. The value of this Beef Calf Vigor Assessment was further emphasized by the negative impacts of failed CC4 on transfer of passive immunity and pre-weaning health.